URGENSI PEMBELAJARAN SENI UNTUK OPTIMALISASI PEMBELAJARAN ANAK USIA DINI: TINJAUAN NEUROSAINS - Nidaa'an Khafiyya; Suyadi Suyadi (UIR PRESS, 2022)
The brain development approach is an important concern in the care and development of early childhood because as it has been previously known that the brain is in control of a human's life. This study aims to determine the urgency of art learning for optimizing early childhood learning in neuroscience review. This type of research is a literature study. Sources of data used in this study are in the form of books, journals, theses, seminar proceedings and others. The results showed that art activities engage all the senses and help regulate the nerves in the brain to process information very well while learning. Incorporating art into learning can activate more regions of the brain. Individuals engaged in art can increase spontaneity and self-expression, control limited inhibitory effects, and produce creative work.